2021
DOI: 10.3390/app11125488
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Choroid Layer Using Deep Learning on Spectral Domain Optical Coherence Tomography

Abstract: The purpose of this article is to evaluate the accuracy of the optical coherence tomography (OCT) measurement of choroidal thickness in healthy eyes using a deep-learning method with the Mask R-CNN model. Thirty EDI-OCT of thirty patients were enrolled. A mask region-based convolutional neural network (Mask R-CNN) model composed of deep residual network (ResNet) and feature pyramid networks (FPNs) with standard convolution and fully connected heads for mask and box prediction, respectively, was used to automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…The major ndings of this study are outlined as follows: (1) The mean choroidal thickness reduced signi cantly for every 20 For our Mask R-CNN model predictions, the mean choroidal thickness was 198.3 ± 58.4 µm, which was lower than that obtained using physician sketches (229.5 ± 70.6 µm). The error observed for our model (8.56 pixels) is slightly higher than the average error (4.56 pixels) observed for a previously proposed model [15]. We noticed found that the prediction error was higher in the 20-39-year group, with thicker choroids, than in the other two groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The major ndings of this study are outlined as follows: (1) The mean choroidal thickness reduced signi cantly for every 20 For our Mask R-CNN model predictions, the mean choroidal thickness was 198.3 ± 58.4 µm, which was lower than that obtained using physician sketches (229.5 ± 70.6 µm). The error observed for our model (8.56 pixels) is slightly higher than the average error (4.56 pixels) observed for a previously proposed model [15]. We noticed found that the prediction error was higher in the 20-39-year group, with thicker choroids, than in the other two groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Hsia et al proposed a Mask R-CNN model for the automatic segmentation of the choroid. They observed that their model could preserve crucial information on location, including shallow and deep layer features, and that it could achieve an accurate prediction rate and faster choroidal boundary segmentation [15]. Overall, Mask R-CNN models are accurate and effective in the automatic segmentation of choroid images.…”
Section: Introductionmentioning
confidence: 99%
“…S2 , n = 6, standard deviation = 4.69 µm). Similar delineation approaches were reported before for retinal 30 33 and choroidal 34 36 segmentation from OCT images. We have measured the mean PChT from each pixel location across the exposed horizontal choroidal area with over 240 axial measurements.…”
Section: Methodssupporting
confidence: 56%
“…In the deep learning side of RLS, [20,21] respectively used Mask R-CNN and a patch-based classifier to segment choroidal boundaries whereas, [22] used a modified Xception network, and [23] adopted a deep feature-learning regression network to detect retinal contours. [24] proposed a combined CNN and LSTM based networks for pre-processing OCT images.…”
Section: Related Workmentioning
confidence: 99%